Boron complexes of aromatic ring fused iminopyrrolyl ligands: synthesis, structure, and luminescence properties. Issue 39 (15th September 2016) - Suresh, D.; Ferreira, Bruno; Lopes, Patrícia S.; Gomes, Clara S. B.; Krishnamoorthy, Paramasivam; Charas, Ana; Vila-Viçosa, Diogo; Morgado, Jorge; Calhorda, Maria José; Maçanita, António L.; Gomes, Pedro T.
Abstract : New fluorescent aromatic ring-fused 2-iminopyrrolyl diphenyl boron complexes are emitters in the range blue to orange. Abstract : The condensation reactions of 2-formylindole (1 ) or 2-formylphenanthro[9, 10- c ]pyrrole (2 ) with various aromatic amines afforded the corresponding phenyl or phenanthrene ring fused mono-/bis-iminopyrrole ligand precursors3–8, which, upon reaction with BPh3 in an appropriate molar ratio, led to the new mono- and diboron chelate compounds Ph2 B[NC8 H5 C(H) N -2, 6-Ar] (Ar = 2, 6-iPr2 C6 H3 9 ; C6 H5 10 ), Ph2 B[(NC8 H5 C(H)N)2 -1, 4-C6 H4 ]BPh2 11, Ph2 B(NC16 H9 C(H) N -Ar) (Ar = 2, 6-iPr2 C6 H3 12 ; C6 H5 13 ), and Ph2 B[(NC16 H9 C(H)N)2 -1, 4-C6 H4 ]BPh2 14, respectively. Boron complexes12–14, containing a phenanthrene fragment fused to the pyrrolyl C3–C4 bond, are highly fluorescent in solution, with quantum efficiencies of 37%, 61% and 58% (in THF), respectively, their emission colours ranging from blue to orange depending on the extension of π-conjugation. Complexes9–11, containing a benzene fragment fused to the pyrrolyl C4–C5 bond, are much weaker emitters, exhibiting quantum efficiencies of 10%, 7% and 6%, respectively. DFT and TDDFT calculations showed that 2, 6-iPr2 C6 H3 N -substituents or, to a smaller extent, the indolyl group prevent a planar geometry of the ligand in the excited state and reveal the existence of a low energy weak band in all the indolyl complexes, which is responsible for the different optical properties. Non-doped single-layer light-emitting diodes (OLEDs) were fabricated with complexes9–14, deposited by spin coating, that of complex13 revealing a maximum luminance of 198 cd m −2 .